Diversidade funcional de grupos bacterianos sob diferentes usos do solo - Bandeira, Leonardo Lima (2020)
Complex interactions between bacteria and soil affect terrestrial biodiversity, ecosystem functions and services. The change in land use also influences important ecosystem functions, including carbon stock, climate regulation, and water cycling, all of which are closely linked to bacterial activities. Understanding the dynamics of bacterial functional groups in the soil is a strategy to infer the state of biodiversity in ecosystems. Thus, the objective of this research was to evaluate how land use affects bacterial functional diversity. The study was carried out in the Sete Cidades National Park. For the collection of the samples, transects were randomly selected in the Conservation Unit, starting from the center of each unit towards the external area and minimum distance between the transects of 3 km. The different types of vegetation cover were selected using the statistical method of random stratification. In total, 28 soil samples were collected from 12 landscapes. The soil samples at each point were collected from rhizospheric soil at a depth of 0 - 20 cm and composed of five sub - samples. Chemical parameters, such as pH and conductivity, and physical parameters, such as sand content, were analyzed. The bacteria were isolated from each soil sample by means of serial dilution and by the spread plate method. Each bacterial group was inoculated in an appropriate culture medium. All counting results were expressed as Colony Forming Units per gram of soil (UFC. G-1) and later converted to Log UFC. g-1. The abundance of the groups and the diversity index were described from the colony counts. The functional diversity of each soil sample was determined using the Shannon index. The abundance of the five functional groups evaluated was higher in the use of agricultural soil, with the group of phosphate solubilizers having the lowest overall abundance of the groups, while the actinobacteria showed the highest abundance. The values of the Shannon index ranged from 1.44 to 1.47, with the preserved and conserved areas having the highest values. As for chemical and physical analysis of soil, agricultural use showed the highest levels of micro and macro nutrients and clay content in the soil. Thus, it is concluded that the change in land use significantly affects the abundance of bacterial communities, mainly in agricultural use. K, Ca, Mg, P, N, Zn and Mn contents in the soil are the nutrients that have a positive and significant correlation with the abundance of bacterial functional groups, while aluminum has a negative correlation with the abundance of these functional groups.